Something In The Walls : a novel - Pearce, Daisy (New York : Minotaur Books, 2025)
"Unbearably tense, utterly propulsive, and studded with folklore and horror, Something in the Walls is perfect for anyone who loves Midsommar and The Haunting of Hill House. Newly-minted child psychologist Mina has little experience. In a field where the first people called are experts, she's been unable to get her feet wet. Instead she aimlessly spends her days stuck in the stifling heat wave sweeping across Britain, and anxiously contemplating her upcoming marriage to careful, precise researcher Oscar. The only reprieve from her small, close world is attending the local bereavement group to mourn her brother's death from years ago. That is, until she meets journalist Sam Hunter at the grief group one day. And he has a proposition for her. Alice Webber is a thirteen year old girl who claims she's being haunted by a witch. Living with her family in their crowded home in the remote village of Banathel, Alice's symptoms are increasingly disturbing, and money is tight. Taking this job will give Mina some experience; Sam will get the scoop of a lifetime; and Alice will get better, Mina is sure of it. But instead of improving, Alice's behavior becomes increasingly inexplicable and intense. The town of Banathel has a deep history of superstition and witchcraft. They believe there is evil in the world. They believe there are ways of...dealing with it. And they don't expect outsiders to understand. As Mina races to uncover the truth behind Alice's condition, the dark cracks of Banathel begin to show. Mina is desperate to understand how deep their sinister traditions go-and how her own past may be the biggest threat of all. "Unexpected, mesmerizing, and totally original...will keep you guessing until its wild end." -#1 International Bestselling author Darby Kane "Harrowing and moving...Pearce has written something magical. There are scenes in this book I'll never forget." -Kristi DeMeester, author of Such a Pretty Smile"--.
new book 2025 fall.
Keywords: Witchcraft; Villages; Horror fiction; Betrothal; Death; Self-help groups; Superstition; Child psychologists; Novels; Thriller fiction; Horror fiction